Visual comparison of Rama’s and Rahwana’s characters in Javanese and Kelantanese wayang kulit - Wibowo, Arif Ardy; Puspita, Ida; Nugroho, Aji Santoso; Nasir, Roziani Mat Nashir @ Mohd; Probosiwi, Probosiwi; Tur, Ajar Pradika Ananta (NOTION: Journal of Linguistics, Literature, and Culture, 2024)
Ramayana, a well-known tale originating from India, has been embraced across Southeast Asia. In regions like Yogyakarta, Indonesia, and Kelantan, Malaysia, local customs have influenced its portrayal, character representation leading to deviations in storyline and. The aim of this study to compare the visual depiction of key characters, particularly Rama and Rahwana, in Javanese and Kelantanese Wayang Kulit, symbolizing the protagonist and antagonist, respectively. This study intends to contribute by revealing the impact of local visual traditions on the enduring grandeur of the Ramayana tale. The method is comparative study, begin with defining data, collecting data from Yogyakarta and Kelantan master of puppets through interview and documentation, analyzing data, displaying data and draw conclusion. The result is found that there are visual similarities and differences related to Rama and Rahwana character. The common visual similarities such as crown, weapon, cloth and accessories. Meanwhile the difference shows that Javanese and Kelantanese is only about the detail of the cloth, the animal rides (Kelantan version), and the size of the Wayang Kulit. In Yogyakarta, Indonesia, and Kelantan, Malaysia, the story of Ramayana is depicted in unique ways, influenced by cultural variations. These distinctions manifest in the characters' looks, headgear, weapon characteristics, facial expressions, and facial coloring. Further investigation is necessary to delve into these differences and understand the puppeteers' role in conveying moral messages to the community.